Non-annual tree rings in a climate-sensitive Prioria copaifera chronology in the Atrato River, Colombia (2015)
Dendrochronology can assign exact calendar years to tree rings. In temperate climates, tree growth dormancy due to low temperatures during winter ensures that the observed tree rings are annual. Thus, it is common practice to assume annual periodicity when: (1) there is common tree growth variability shared among trees; (2) significant correlations with meteorological records with anual resolution are found. Here, we show how these criteria are not valid for trees of the tropical species Prioria copaifera Griseb., located at the Atrato River in Colombia (~ 5°N). Using dendrochronological procedures, we were able to generate a reliable tree ring-width chronology that correlated significantly with several environmental variables from the region. However, 24 radiocarbon measurements from three trees demonstrated offsets of up to 40 years that indicates that P. copaifera can produce more than one ring in certain years. This led to the conclusion that anatomical features defining tree rings were not distinguishable as being either annual or subannual. Results derived from a growth model and the instabilities found in the climate-growth relationship suggest that the climatic signal found may be due to the fact that some of the tres show annual rings for the last years when analyses were performed, however, spurious significant correlations cannot be discarded. Radiocarbon measurements done before and after the bomb spike in multiple trees are an useful and independent method to validate the identification of annual tree rings when tropical species show challenging anatomical features defining the boundaries of the growth layers.